New taxa of giant caimans from the southernmost hyperdiverse wetlands of the South American late Miocene - Bona, Paula; Barrios, Francisco; Ezcurra, Martín Daniel; Fernandez Blanco, María Victoria; Cidade, Giovanne Mendes [UNESP] (Taylor & Francis, 2024)
Here we present a comparative anatomical study of large late Miocene alligatorids of Argentina (Ituzaingó Formation), in which we analyse their taxonomy, morphological disparity, and phylogenetic relationships. ‘Caiman lutescens’ and Caiman gasparinae are two giant Miocene Argentinean caimanines that are assigned to the genus Caiman. ‘Caiman lutescens’ was originally described based on the large size of several isolated cranial and postcranial elements. In this study we consider that the lectotype of ‘C. lutescens’, an articulated left premaxilla and maxilla (MACN-Pv 5416), is morphologically indistinguishable from rostral morphotypes present in other jacarean caimanines, like Caiman latirostris and Caiman wannlangstoni, and therefore ‘C. lutescens’ is here considered a nomen dubium while MACN-Pv 5416 is an indeterminate Jacarea. A partial skull table, MACN-Pv 13551, was originally and historically referred to ‘C. lutescens’, and even wrongly considered its holotype, but it is here redescribed and reinterpreted as the holotype of a new genus and species. Additionally, after the comparative anatomical study of the holotype of C. gasparinae(MLP-Pv 73-IV-15-1), we conclude that it shows a distinctive combination of skull morphological features that allows it to be distinguished from other caimanines, including extant Caiman species. This situation and the results of the phylogenetic analyses lead us to erect a new genus for this species, which results in a new nomenclatorial combination. These new results support the idea that the alligatorid assemblages of the South American late Miocene wetlands were highly diverse at high latitudes (c. 30–35°S), as evidenced by the taxonomic diversity and morphological disparity present in the crocodylian assemblage of the Ituzaingó Formation in Paraná. The close relationship between the two new taxa + Mourasuchus spp. with Purussaurus spp. recovered in the present study reinstates the question of how to define the Caiman genus, as well as when and where it originated. http://zoobank.org/urn:lsid:zoobank.org:pub:6096F826-7CCA-4795-B4CF-5AFF87D6EBCC.
Keywords: Caimaninae; Crocodyliformes; Ituzaingó Formation; Neogene; South America; wetlands